Immune Responses to Collagen‐IV and Fibronectin in Renal Transplant Recipients With Transplant Glomerulopathy. Issue 3 (10th January 2014) - Angaswamy, N.; Klein, C.; Tiriveedhi, V.; Gaut, J.; Anwar, S.; Rossi, A.; Phelan, D.; Wellen, J. R.; Shenoy, S.; Chapman, W. C.; Mohanakumar, T.
ABSTRACT Antibodies (Abs) to donor HLA (donor‐specific antibodies [DSA]) have been associated with transplant glomerulopathy (TG) following kidney transplantation (KTx). Immune responses to tissue‐restricted self‐antigens (self‐Ags) have been proposed to play a role in chronic rejection. We determined whether KTx with TG have immune responses to self‐Ags, Collagen‐IV (Col‐IV) and fibronectin (FN). DSA were determined by solid phase assay, Abs against Col‐IV and FN by enzyme‐linked immunosorbent assay and CD4+ T cells secreting interferon gamma (IFN‐γ), IL‐17 or IL‐10 by ELISPOT. Development of Abs to self‐Ags following KTx increased the risk for TG with an odds ratio of 22 (p‐value = 0.001). Abs to self‐Ags were IgG and IgM isotypes. Pretransplant Abs to self‐Ags increased the risk of TG (22% vs. 10%, p < 0.05). Abs to self‐Ags were identified frequently in KTx with DSA. TG patients demonstrated increased Col‐IV and FN specific CD4+ T cells secreting IFN‐γ and IL‐17 with reduction in IL‐10. We conclude that development of Abs to self‐Ags is a risk factor and having both DSA and Abs to self‐Ags increases the risk for TG. The increased frequency of self‐Ag‐specific IFN‐γ and IL‐17 cells with reduction in IL‐10 demonstrate tolerance breakdown to self‐Ags which we propose play a role in the pathogenesis of TG.